A Story on SPACs - Milan Lakicevic; Milos Vulanovic (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
We study characteristics of Specified Purpose Acquisition Companies (SPACs) and examine the performance of their securities over time. We find that SPACs represent a fairly unique way to raise capital. The incentives of their founders, underwriters, and investors are interdependent and successful business combinations generally result in significant returns to founders. We also show that different SPAC securities generate different reactions in response to the announcement news regarding their corporate status. While holders of all three securities realize abnormal returns on the announcement day, the strongest reaction is observed among the investors holding warrants, while common stock holders tend to react very mildly.
Keywords: G32; 330; SPACs; Blank Checks; Venture Capital; IPO's; Warrants; Reverse Mergers